Growth conditions and uniqueness of the Cauchy problem for the evolutionary infinity Laplacian - Leonori, Tommaso (2008)
We study the Cauchy problem for the parabolic infinity Laplace equation. We prove a new comparison principle and obtain uniqueness of viscosity solutions in the class of functions with a polinomial growth at infinity, improving previous results obtained assuming a linear growth.